Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Produktivitas Karyawan Dengan Keselamatan Kesehatan Kerja (K3) Sebagai Variabel Intervening - Taufik Kurrohman; Suwarto; Fitriani (Universitas Muhammadiyah Metro, 2025)
In a company there are many things that must be paid attention to, just as a company must pay a lot of attention to the productivity of its employees so that they continue to run well and get maximum results in accordance with the responsibilities given to them. To achieve good productivity in today's increasingly advanced digital era, companies must be able to change dynamically and be competitive in the competition. Therefore, efforts to increase employee productivity are the most serious management challenges, because success in achieving a goal and the survival of the company depends on the quality of human productivity within it. This research aims to determine the direct influence of the work environment on Occupational Health and Safety (K3). To determine the direct influence of work discipline on Occupational Health Safety (K3). To determine the direct influence of the work environment on productivity. To determine the direct influence of work discipline on productivity. To find out the direct influence of Occupational Health Safety (K3) on productivity. The sample for this research was all employees at PT Sarana Cahaya Makmur, totaling 40 people. Data collection uses questionnaires and literature studies, and data analysis includes validity tests, reliability tests, normality tests, linearity tests, homogeneity tests, and path analysis using (SPSS). The research results show that there is a positive and significant influence of the work environment on employee productivity. There is a positive and significant influence of Work Discipline on Employee Productivity. There is a positive and significant influence of the Work Environment on Occupational Health Safety (K3). There is a positive and significant influence of Work Discipline on Occupational Health Safety (K3). There is a positive and significant influence of Occupational Health Safety (K3) on Employee Productivity. There is a positive and significant influence of the Work Environment, Work Discipline, and Occupational Health and Safety (K3) on Employee Productivity.